The use of the Kahoot Platform in Teaching-Learning English Vocabulary for Second-Year Students, Faculty of Linguistics, Souphanouvong University - vandalak, phonesavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to: (1) examine the efficiency of using the Kahoot platform in teaching English vocabulary based on the 70/70 criterion, (2) investigate its effectiveness in enhancing students’ learning outcomes, and (3) explore students’ attitudes toward its use. The target group consisted of 40 second-year students from the Faculty of Linguistics at Souphanouvong University in the academic year 2025–2026. The research instruments included lesson plans integrating Kahoot, pre- and post-tests, and an attitude questionnaire. Data were analyzed using efficiency values (E1/E2), mean, standard deviation, percentage, and the Effectiveness Index (E.I.). The results showed that the efficiency of the Kahoot-based instruction was 80.5/90.5 (E1/E2), which exceeded the established 70/70 criterion. The Effectiveness Index was 0.6691 (66.91%), indicating a significant improvement in students’ learning achievement after instruction. Regarding students’ attitudes, the overall level was very high ( = 4.13, SD = 0.79). Students reported very positive attitudes toward the learning environment, learning activities, and the application of Kahoot in vocabulary learning.